Curated Decay: Residual Industrialization at the Nova Scotia Museum of Industry - McInnis, Peter S. (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2023)
Nova Scotians understand economic hardships at both the personal and community levels. This is especially true for the residents of Pictou County. With the eclipse of coal, steel, and heavy manufacturing, successive governments looked to tourism to augment an eroding economic base and to commemorate the working lives of Nova Scotians. This article offers an analysis of the initial decision to construct and maintain the Museum of Industry in a region of the province subjected to sequential phases of deindustrialization. The venture, officially opened to regular attendance in 1995, is the largest facility in the province’s impressive system of 28 regional museums. The creation of the museum, however, was fraught with uncertainty and narrowly avoided financial collapse and plans to disperse the collection of artifacts. The project was subsequently left straddling an uneasy divide between celebrating industrial heritage and tempering controversies of economic and environmental development. Despite Nova Scotia’s proud heritage of worker resistance and union activism, visitors may exit the museum with the ambiguous message that while working lives are often harsh and riven with uncertainty, optimism for the future must prevail. The implication is that the appropriate response is selective anodyne forms of nostalgia, even resignation, but not resentment of the human and environmental costs of deindustrialization.